Introduction to the epidemiologic considerations, analytic methods, and foundational results from the pneumonia etiology research for child health study - O’Brien, KL; Baggett, HC; Brooks, WA; Feikin, DR; Hammitt, LL; Howie, SRC; Knoll, M; Kotloff, KL; Levine, OS; Madhi, SA; Murdoch, DR; Scott, JAG; et al. (Oxford University Press, 2017)
Over the last 20–30 years, enormous reductions have occurred in the absolute and relative burden of pneumonia mortality in young children around the world. Only 20 years ago, when the population of young children was approximately 625 million, approximately 1.7 million young children died from pneumonia before their 5th birthday (Figure 1) [1–4]. Mortality from pneumonia among children aged <5 years fell to 921 000 in 2015, whereas the population of young children rose to >670 million [1, 2, 5]. This remarkable improvement in child survival and health has resulted from advances in social conditions and economic development [6] but has also been influenced by at least 4 pivotal innovations: (1) the development of a global vaccination program, the World Health Organization’s Expanded Program on Immunizations (begun in 1974), which created the architecture around which country investments, donor funding, program strategies, and outcome measurements could be envisioned and implemented; (2) the global consensus to focus funding, programs, and momentum on 6 development targets articulated by the United Nations General Assembly through the Millennium Development Goals (MDGs, agreed upon in 2000) with MDG4 targeting child survival; (3) the advent of large, health-focused nongovernmental organizations; and (4) the founding of the Global Alliance for Vaccines and Immunization (the Gavi Alliance, formally launched at the World Economic Forum in January 2000), a multilateral funding organization that has allowed for an unprecedented pace of introduction and expanded use of life-saving vaccines in low-income countries. In part, as a result of this multidimensional, multisectoral consensus approach enacted through critical large-scale investments in prevention, protection, and treatment, pneumonia mortality has fallen substantially in many parts of the world because the most fatal of the pathogens and the underlying conditions that put children at risk are being targeted.